Net Section Fracture Assessment of Welded Rectangular Hollow Structural Sections - Abedin, Mohammad; Kiani, Nafiseh; Shahrokhinasab, Esmail; Mokhtari, Sohrab (Salehan Institute of Higher Education, 2020)
Rectangular Hollow Sections (RHS) because of their high resistance to tension, as well as compression, are commonly used as a bracing member with slotted gusset plate connections in steel structures. Since in this type of connection only part of the section contributes in transferring the tensile load to the gusset plate, shear lag failure may occur in the connection. The AISC specification decreases the effective section net area by a factor to consider the effect of shear lag for a limited connection configuration. This study investigates the effective parameters on the shear lag phenomenon for rectangular hollow section members connected at corners using a single concentric gusset plate. The results of the numerical analysis show that the connection length and connection eccentricity are the only effective parameters in the shear lag, and the effect of gusset plate thickness is negligible because of the symmetric connection. The ultimate tensile capacity of the suggested connection in this study were compared to the typical RHS connection presented in the AISC and the similar double angle sections connected at both legs. The comparison indicates that tensile performance of the suggested connection in this study because of its lower connection eccentricity is much higher than the typical slotted connection and double angle connections. Therefore, a new equation is suggested based on the finite element analyses to modify the AISC equation for these connections.